Product Binary L-Cordial Labeling of Various Degree Splitting Graphs - Prajapati, U. M.; Patel, P. A. (Communications in Mathematics and Applications, 2024)
This study examines the probability of the degree splitting operation results from various graphs being product binary \(L\)-cordial graphs. The graphs under investigation include the path graph \((P_{n})\), comb graph \((P_{n}\odot k_{1})\), double comb graph \((P_{n}\odot 2k_{1})\), cycle graph \((C_{n})\), shell graph \((S_{n})\) and ladder graph \((L_{n})\). The application of product binary \(L\)-cordial labelling demonstrates that these analyzed graphs exhibit characteristics of product binary \(L\)-cordial graphs.